2019
DOI: 10.1111/cmi.13119
|View full text |Cite
|
Sign up to set email alerts
|

Not lost in host translation: The new roles of long noncoding RNAs in infectious diseases

Abstract: Long non‐coding RNAs (lncRNAs) play a central role in the regulation of gene expression. Although they were initially described as mRNA‐like transcripts not encoding proteins, global approaches such as ribosome profiling have shown that they frequently associate with ribosomes, opening the possibility that lncRNAs are a source of cryptic translation events with functional roles. Recent studies have shed more light on small ORFs borne by lncRNAs and encoding short peptides potentially involved in infectious imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Long non‐coding RNAs (lncRNAs) are classically defined as RNA transcripts larger than 200 nucleotides but lack of protein coding capacity 13 . LncRNAs have been unravelled to exert their functions via modulating chromatin remodelling, transcription regulation, post‐transcriptional modifications and signal transduction 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long non‐coding RNAs (lncRNAs) are classically defined as RNA transcripts larger than 200 nucleotides but lack of protein coding capacity 13 . LncRNAs have been unravelled to exert their functions via modulating chromatin remodelling, transcription regulation, post‐transcriptional modifications and signal transduction 14 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Nevertheless, EMT is a complicated process associated with tumorigenesis, 12 Long non-coding RNAs (lncRNAs) are classically defined as RNA transcripts larger than 200 nucleotides but lack of protein coding capacity. 13 LncRNAs have been unravelled to exert their functions via modulating chromatin remodelling, transcription regulation, post-transcriptional modifications and signal transduction. 14 It has been shown that lncRNAs play crucial regulatory roles in various biological functions, including cell growth, differentiation, migration, invasion and EMT programs.…”
mentioning
confidence: 99%
“…In the realm of RNA research, certain studies consider arbitrarily those RNAs with their largest ORF shorter than 100 codons or 300 nts as long non-coding RNAs (25)(26)(27)(28)(29), while other studies define long non-coding RNAs more stringently with 200 nts as the arbitrary cut-off (30)(31)(32). The present study (8,10,33), along with many others (34,35), argue against these existing definitions as numerous studies have demonstrated that very short peptides [as short as 11 AAs encoded by only 33 nts (36-39)] have important functions. Therefore, numerous RNAs, including virtually all mRNAs, may function through translation into proteins or short peptides and through one of the several known non-coding mechanisms (including miRNA or siRNA mechanisms), with the steroid receptor RNA activator being the first known example of such dual mechanisms (40).…”
Section: Discussionmentioning
confidence: 86%
“…Over the past decades, lncRNAs have been initially described as transcripts that cannot encode proteins or peptides [ 11 , 12 ]. With the development of bioinformatics and high‐throughput transcriptomics and proteomics approaches including ribosome profiling, ribosome sequencing, and mass spectrometry (MS) analysis, accumulating lncRNAs have been recognized to be RNA molecules with open reading frames (ORFs) and peptide/protein‐coding potential [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%